2016
DOI: 10.1159/000450650
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Splicing in Cancer: Mediators of Malignant Progression through an Imperfect Splice Program Shift

Abstract: Although the efforts to understand the genetic basis of cancer allowed advances in diagnosis and therapy, little is known about other molecular bases. Splicing is a key event in gene expression, controlling the excision of introns decoded inside genes and being responsible for 80% of the proteome amplification through events of alternative splicing. Growing data from the last decade point to deregulation of splicing events as crucial in carcinogenesis and tumor progression. Several alterations in splicing even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In fact, for them (as well as many other proteins), it was shown that an aberration in any part of the cellular machinery generating proteoforms (which are the basis of the existence of the protein structure–function continuum) might have some disastrous consequences [194]. For example, it is now recognized that deregulation of splicing events (via mutations or misexpression of some splicing factors) is a crucial trigger and initiator of carcinogenesis and tumor progression [257]. Obviously, this list can be further extended to include almost any protein.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, for them (as well as many other proteins), it was shown that an aberration in any part of the cellular machinery generating proteoforms (which are the basis of the existence of the protein structure–function continuum) might have some disastrous consequences [194]. For example, it is now recognized that deregulation of splicing events (via mutations or misexpression of some splicing factors) is a crucial trigger and initiator of carcinogenesis and tumor progression [257]. Obviously, this list can be further extended to include almost any protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one important aim of the present study was to identify biomarkers for predicting therapeutic response and prognosis, which may provide a deeper understanding of the tumor biology (1,2). To date, numerous molecular events, including those at the epigenetic, pre-transcriptional, transcriptional, translational and post-translational levels, have been identified and validated as important prognostic biomarkers (3), such as the Ki-67 protein and TP53 gene mutations. However, the functional significance of cancer-specific alternative splicing (AS) events is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, growing data has indicated that the dysregulation of AS is a crucial event in carcinogenesis and tumor progression (3,(7)(8)(9). Genes with aberrant AS events are involved in almost every aspect of cancer, including…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is potentially an attractive one in cancer as well, because it is well known that tumors often have misregulated splicing that could potentially be corrected by this approach. 88 …”
Section: Splice Modulating Asosmentioning
confidence: 99%